2014
DOI: 10.1128/jcm.00162-14
|View full text |Cite
|
Sign up to set email alerts
|

Travel-Related Carbapenemase-Producing Gram-Negative Bacteria in Alberta, Canada: the First 3 Years

Abstract: We describe here the characteristics of Alberta, Canada, patients with infections or colonizations with carbapenemase-producing Gram-negative bacteria during 2010 to 2013 that were linked to recent travel outside Canada. Antimicrobial susceptibility was determined by broth microdilution, and isolates were characterized using PCR, sequencing, and multilocus sequencing typing. A broth mating study was used to assess the transferability of resistance plasmids, which were subsequently characterized. All the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 45 publications
2
46
1
1
Order By: Relevance
“…ST10 and ST58 have both a global distribution, and they have been isolated from humans as well as animals (41)(42)(43)(44). The K. pneumoniae outbreak in Uppsala was also caused by a global clone, ST16 (12), which in recent years has been associated with several clinically important carbapenemases (45). Interestingly, it has been suggested that resistance to silver ions represents a potent fitness factor in members of the Enterobacter cloacae complex (46).…”
Section: Discussionmentioning
confidence: 99%
“…ST10 and ST58 have both a global distribution, and they have been isolated from humans as well as animals (41)(42)(43)(44). The K. pneumoniae outbreak in Uppsala was also caused by a global clone, ST16 (12), which in recent years has been associated with several clinically important carbapenemases (45). Interestingly, it has been suggested that resistance to silver ions represents a potent fitness factor in members of the Enterobacter cloacae complex (46).…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was in a Citrobacter freundii strain; bla NDM-1 was not detected on the plasmid carrying bla OXA-181 , suggesting that bla NDM-1 is likely located on a different plasmid. It would be interesting to explore whether bla NDM-1 was located on an IncX3 plasmid within those strains carrying bla NDM-1 and bla OXA-181 (9,10,12,(15)(16)(17)29). On the other hand, as WCHEC14828 has no bla NDM-1 , it may also be possible that an IncX3 plasmid carrying bla OXA-181 has replaced the IncX3 plasmid carrying bla NDM-1 due to plasmid incompatibility.…”
mentioning
confidence: 99%
“…To date, carbapenemase-producing Gram-negative bacilli remain uncommon in Canada. VIM-, NDM-, and OXA-producing isolates have been reported infrequently in case reports, with acquisition often linked to travel (Mataseje et al, 2013;Mulvey et al, 2011;Peirano et al, 2011Peirano et al, , 2014Pitout et al, 2007;Sepehri et al, 2014;Tijet et al, 2013). A nosocomial outbreak of VIM producing P. aeruginosa has been documented in the Canadian province of Alberta (Pitout et al, 2007).…”
Section: Discussionmentioning
confidence: 95%